Saberes andino-campesinos: apuesta agrocultural para el cuidado y revalorización del suelo como patrimonio natural Cali - Colombia (2018)
The present investigation called, an agrocultural betting for the Andean soil conservation as a natural heritage, is located in the Santiago de Cali rural context, on the pathway La Esperanza from the small town of Felidia. The soil in the plot of conventional agriculture, has been reduced to a chemical vision, product of the green revolution, the soil in mountainous regions have been losing vertiginously, is for this reason that this investigation of social and environmental court pretends to make an input from the Andean-farmer’s knowledge to reconfigure the concept and the practice of what the care of the soil implies. For this purpose characterization of the productive system has been made from a farm. In this way and from different analysis made like the soil’s chromatography, nourishment and fertilizers, paramagnetic reading of the soil, physical-chemical analysis of wáter and ground, microbiological analysis, knowledge dialogue, it can be said that the production model hasn’t been a sustainable proposal where completely healthy foods can’t be obtained, in terms of soil conservation and agrarian processes. This is reflected in the loss of the structure of the ground and its quality, based on the review of the components of this project in the field, the MCASA (Community Manual for Agroculture for Andean Soils) it’s proposed, that tries to resignify the concept of the soil as an alive and complex system. For this, alternative process must be generated and implement alternative agriculture whose purpose is the regeneration of the natural environment and the territory’s harmonization